(untitled) (Al-Academy, 2018)
Most of the theorists and researchers and also those interested in cinema and television attributed the fact of the existence of the dramatic works to the directors may be due to a historical justification. At the same time, the existence of the production world came as a result of the emergence of the production city (Hollywood). This is also a historic fact. The research would tackle all the formative truths to prove the relation and the timeline, i.e., before and after and the synergy that resulted in the existence of the dramatic works that benefited the humanity and those interested in this giving art. The objective of the research is to uncover the formative truth of the dramatic work between direction and production. The study dealt with a theoretical foundation made of two sections: the first is (the historical controversy between the cinematic and television direction and production) and the second is (the formative truth of the existence of the dramatic works between direction and production). Throughout the research, important facts have been reached at, such as due to the fact that the formative start for the existence of the dramatic works was initiated by the producers, yet the directors were also present in that period of time. The role of the producer, who throughout the years helped both the directors and the humanity in general, and produces the best distinctive works in the ancient and modern history, cannot be ignored. The producer, as a result, is the one who illuminated the way and clarified the synergetic relation and the formative truth of the dramatic works between the direction and production.